2020
DOI: 10.4103/aam.aam_57_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prescription pattern of analgesic use among ambulatory elderly in South-Western Nigeria

Abstract: Background: Inappropriate prescribing of analgesics has a global impact on the health of elderly patients and the society. Empirical evidence on the prescription of analgesics among elderly Nigerians is scarce. Objectives: The objective of the study was to evaluate the prescription pattern of analgesics and describe the co-prescribing of gastroprotective agents with non-steroidal anti-inflammatory drugs (NSAIDs) among elderly patients at the geriatric center, University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…and Ragaven, L.B., 2020 (15%). 32 Our result somewhat contrasted with the findings of Irshaid et al, Balbaid and Al-Dawood, and Makonnen et al 30,33,34 The study has revealed a high propensity to omit required information (like. starting date of a drug, signature of prescribing doctor, dose, dosage form, strength, route, drug spellings etc.)…”
Section: Prescription Errorscontrasting
confidence: 87%
See 1 more Smart Citation
“…and Ragaven, L.B., 2020 (15%). 32 Our result somewhat contrasted with the findings of Irshaid et al, Balbaid and Al-Dawood, and Makonnen et al 30,33,34 The study has revealed a high propensity to omit required information (like. starting date of a drug, signature of prescribing doctor, dose, dosage form, strength, route, drug spellings etc.)…”
Section: Prescription Errorscontrasting
confidence: 87%
“…In our study, 35.88% of the prescription were illegible prescription, which was due to the poor handwriting that may lead to dispensing the wrong medications. These results of studies are contrasted with those reported by Al Slamah, Thamer., et al (64.3%), 30 Tobaiqy, M. and Stewart, D, (7.2%) 31 and Nkera-Gutabara, J.G. and Ragaven, L.B., 2020 (15%).…”
Section: Prescription Errorsmentioning
confidence: 97%
“…Acetaminophen, ASA, and diclofenac were the most frequently prescribed anti-inflammatory agents in the general population in such regions, as well as in the geriatric and pediatric patients. [22][23][24] It has been posed that the high prevalence of discarded anti-inflammatory drugs might derive from a steady increase in the geriatric population and the tendency of the elderly to use a greater amount of NSAIDs compared to other age groups in the population. 14) Whatever the cause may be of the high prevalence of the prescription and purchase of AAMs, the focus of the current contribution is the tendency of these drugs to accumulate in homes.…”
Section: Discussionmentioning
confidence: 99%
“… 164 , 165 Physicians should note a detailed history of previous and current medications, including herbal medicines. 166 Individuals should be counseled to avoid alternative medicines, especially those with a known risk of renal damage or with known drug interactions.…”
Section: Framework For Treatment Goals Of Ckdmentioning
confidence: 99%